High-intensity focused ultrasound treatment for large and small solitary uterine fibroids. (31st December 2022) - Chang, Chih-Ting; Jeng, Cherng-Jye; Long, Cheng-Yu; Chuang, Linus T.; Shen, Jenta
Abstract: This retrospective study used data from patients treated for uterine fibroids with ultrasound-guided high-intensity focused ultrasound (USgHIFU) from April 2015 to April 2019. One hundred and seven patients with solitary fibroids were divided into two groups: (1) the L group with larger fibroids (≥10 cm) and (2) the S group with smaller fibroids (<10 cm). Using magnetic resonance imaging (MRI), we examined the efficacy of high-intensity focused ultrasound (HIFU) ablation by comparing uterine and fibroid volumes before and three months after the procedure. The three-month follow-up clinical visit used a visual analog scale and a uterine fibroid symptom health-related quality of life questionnaire to evaluate clinical symptoms. Both the L and S groups had significant reduction in uterine and fibroid volumes, but the rate was significantly higher in the S group ( p < 0.05). Both groups also had improvements in clinical symptoms, but there was no statistical difference. USgHIFU reduced the size of both large and small fibroids but was most effective on fibroids smaller than 10 cm. Both the L and S groups had improved dysmenorrhea symptoms and quality of life.